التقييم الكيميائي والفيزيائي لجودة مياه الشرب بوحدات التنقية في المحلات التجارية دراسة حالة: (بلدية العزيزية – ليبيا) (Comprehensive Journal of Science, 2026)
This study aimed to evaluate the quality of drinking water produced by desalination stations relying on groundwater sources in the study area. A set of physico-chemical parameters was analyzed, including Total Dissolved Solids (TDS), Electrical Conductivity (EC), pH, and major ions such as calcium, magnesium, sodium, chlorides, sulfates, and bicarbonates.Ten water samples were collected from local drinking water filling shops and analyzed using standard laboratory procedures. The results indicated that most samples complied with the maximum permissible limits of national standards. However, a noticeable reduction in mineral content was observed, as TDS and essential mineral concentrations were below the minimum recommended levels in several cases. The average pH value was also found to be lower than the acceptable range, reflecting reduced buffering capacity due to reverse osmosis treatment without remineralization.Comparison with previous Libyan studies revealed a recurring pattern of low mineralization in desalinated and bottled drinking water. The study recommends the implementation of a remineralization stage and pH adjustment processes, along with strengthened regulatory monitoring, to ensure balanced mineral composition and sustainable drinking water quality.
Keywords: Drinking water quality; Desalination; Reverse osmosis; Total dissolved solids; pH; Remineralization; Groundwater; Libyan standards.